Can green investment improve China’s regional energy consumption structure? novel findings and implications from sustainable energy systems perspective - Zhengyuan Liu; Zhengyuan Liu; Johnny F. I. Lam; Hongxi Chen; Hongxi Chen; Guochao Lin; Huangxin Chen (Frontiers in Energy Research, 2023)
Green investment can promote the low-carbon development of energy consumption structure in direct and indirect ways through financial support for new energy industry and pulling effect on environmental protection industry, which is of great significance to the sustainable development of economy and society. Through empirical analysis of the panel data of provinces and municipalities in China, this paper finds that the impact of green investment on the energy consumption structure is highly differentiated between regions: the development of green investment in the eastern region will inhibit the increase of the proportion of coal and other polluting energy sources in the energy consumption structure, which will help the energy consumption structure tend to develop in a decarbonized way; in the central region, the impact of green investment on the energy consumption structure is insignificant; and in the western region, green investment instead promotes the development of the energy consumption structure in a decarbonized way. In the western region, green investment instead promotes the proportion of coal and other polluting energy in the energy consumption structure. The main reason for this is that there are big differences in the level of economic development, characteristics of industrial structure, population size and technological level between the East, the Middle East and the West. It is an important measure to strengthen green investment and improve energy consumption structure to dynamically adjust green development goals, strengthen financial support for energy conservation and environmental protection industries, and narrow the regional development gap in all directions.